PERLINDUNGAN HUKUM TERHADAP LESSOR PASCA DIKELUARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR 11 TAHUN 2020 - Muhammad Fakhri Adlan (2021)
ABSTRACT There are several financial institutions, which is leasing. In the lease agreement there is a risk that becomes an obstacle in the lease agreement, caused by the lessee. This article (Journal) to find out the responsibilities of the lessee in the lease agreement, understand the legal protection of the lessor when the lease agreement is executed in cases of breach of contract committed by the lessee, how to resolve disputes in cases of breach of the lessee's contract. This type of research is normative legal research. Using legal methods. The legal materials used are primary and secondary legal. The lease agreement stems from the principle of contract freedom as regulated in Article 1338 of the Civil that the agreement is legally valid for the agreement. If the lessee violates the contract, then the legal protection of the lessor is weak, and the protection of the parties is limited in the lease agreement the risk is to define detailed and clear requirements in the lease agreement, to ensure that the organization can protect the interests of the lessor. In addition, the lessor can, in accordance with the provisions of Article 1249, a penalty as a form of compensation for breach of contract by the lessee, that the lessee contract, provides legal protection for lessor when executing the lease agreement. It appears that proper procedures will protect the lessor, and the lessor will not be disadvantaged. Keywords :. legal protection, leasing, lessor, lessee;